L’anthropologie comme philosophie - Philippe Sabot (Methodos, 2005)
The article aims to examine the sort of philosophical critic of religion that Feuerbach notably offers in L’essence du christianisme. This critic is about the production of religious illusion wich depends on a paradoxal objectivation and alienation process : man’s selfconsciousness is accompanied by the projection of a fictitious Other (God), considered as its ontological and practical guarantee. By analyzing this reversal process and its subject-object dialectics, Feuerbach points out the anthropological foundations of religious consciousness, but he also develops the problematic theme of a mankind’s religion, wich is at the origin of modern “atheistic humanism” (H. de Lubac).